A random forest model for predicting the crystallisability of organic molecules1. Issue 23 (21st June 2015) - Bhardwaj, Rajni M.; Johnston, Andrea; Johnston, Blair F.; Florence, Alastair J.
<x xml:space="preserve">Abstract</x> A random forest model has for the first time enabled the prediction of the crystallisability (crystals vs. no crystals) of organic molecules with ~70% accuracy. The predictive model is based on calculated molecular descriptors and published experimental crystallisation propensities of a library of substituted acylanilides.